Interface morphology snapshots of vertically segregated thin films of semiconducting polymer/polystyrene blends - Castro, Fernando A.; Graeff, Carlos Frederico de Oliveira [UNESP]; Heier, Jakob; Hany, Roland (Elsevier B.V., 2007)
We present atomic force microscopic images of the interphase morphology of vertically segregated thin films spin coated from two-component mixtures of poly[2-methoxy-5-(2'-ethylhexyloxy)-1,4-phenylene-vinylene] (MEH-PPV) and polystyrene (PS). We investigate the mechanism leading to the formation of wetting layers and lateral structures during spin coating using different PS molecular weights, solvents and blend compositions. Spinodal decomposition competes with the formation of surface enrichment layers. The spinodal wavelength as a function of PS molecular weight follows a power-law similar to bulk-like spinodal decomposition. Our experimental results indicate that length scales of interface topographical features can be adjusted from the nanometer to micrometer range. The importance of controlled arrangement of semiconducting polymers in thin film geometries for organic optoelectronic device applications is discussed. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: polymer demixing; polymer blends; MEH-PPV